Separation of Hydrogen Isotopes Mixtures Using Different Concentrations of Gas Mixtures by Gas Chromatography - PREDA, ANISOARA; PEARSICA, CLAUDIA; VASUT, FELICIA; BARBU, CRISTINA; POPESCU, ALEXANDRU (Asian Journal of Chemistry, 2010)
In this paper, method gas chromatography for the analysis of the different concentrations of gas mixtures containing hydrogen isotopes. The method described in this paper was based on using a capillary molecular sieve 5A column which has been operated at 174 K. The isotopic species of hydrogen are: H2, D2, T2, HD, HT, DT, ortho-H2, para-H2, ortho-D2 or para-D2, where D stands for 2H and T for 3H. In all cases, the p-H2 (para-H2) form appears before the ortho- form. These forms are presented in our chromatograms. We used a gas mixture with the next isotopic species of hydrogen H2, D2, HD, ortho-H2, para- H2. Ortho- and para-deuterium are not so easily separated. In this way ortho-deuterium appearing first. This paper discusses about the specific design of the gas chromatograph and presents the chromatograms measured for different concentrations of isotopic species of hydrogen gas mixture.